ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN SAK EMKM PADA USAHA KECIL, MIKRO DAN MENENGAH DI KABUPATEN BANYUMAS - Sully Kemala Octisari; Tjahjani Murdijaningsih (FEB UNWIKU PURWOKERTO, 2020)
Micro, Small and Medium Enterprises (SMMEs) are people's business activities which are currently the backbone of the Indonesian economy. To simplify the process of preparing MSME financial reports, currently a special Financial Standard for SMMEs has been formalized which is named the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). This study aims to examine what factors influence the implementation of SAK EMKM in Banyumas Regency. These factors include the provision of information and outreach, educational background, level of education, length of business and size of business. The study was conducted by distributing questionnaires with 62 questionnaires that can be used for research. Data were tested using Multiple Regression Analysis. The test results show that partially, the owner's education level has an effect on the implementation of SAK EMKM, the provision of information and outreach has a significant and positive effect on the implementation of SAK EMKM, while the understanding of information technology and business age does not have a significant effect on the implementation of SAK EMKM in SMMEs in the district. Banyumas.